Smart Laundry System (SLS) Enterprise: smart card laundry system / Nur Hazirah Abd Kongid... [et al.] - Abd Kongid, Nur Hazirah; Zainal Abidin, Nasrin Nasuha; Mohd Zulkimi, Noor Fazreena; Illias, Nornadjwa; Harman Shah, Nor Alya Maisara (2017)
Smart Laundry System Enterprise (SLS Etp) is a company that introduced and producing a technology like the name given for the business which is a smart laundry system. For this business which is the owner's of the self-service laundry especially that has a 24 hours service.